Women as winners : transactional analysis for personal growth/ by Dorothy Jongeward and Dru Scott - "Jongeward,Dorothy" (London, 1976)
Women as winner is a practical and positive book for women and men who are ready to better understand the dynamic and perplexing changes facing women. It is for people who are ready to help women move in positive directions towards wholeness.
Keywords: Women-Psyhcology